2013
DOI: 10.1097/ncc.0b013e31826a7235
|View full text |Cite
|
Sign up to set email alerts
|

The Social Construction of Cancer Chemotherapy Toxicity

Abstract: The disparity of perceptions between healthcare professionals and patients regarding chemotherapy toxicity needs to be thoroughly assessed. Thus, culturally specific nursing care models may be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Previously, conventional antimicrobial therapy adopted an ascending stepwise model, which has been shown to be effective in patients with mild infections. However, for severe infection cases, despite certain mitigation on the APACHE II score and inflammatory response [ 15 ], it is mostly substituted by cephalosporins with higher potency due to its suboptimal efficacy, which increases the risk of adverse effects and the development of drug-resistant bacteria [ 16 ]. As a result, “step-down treatment” was recommended as a sensible medication approach for antimicrobial drug usage in ICU patients with severe bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, conventional antimicrobial therapy adopted an ascending stepwise model, which has been shown to be effective in patients with mild infections. However, for severe infection cases, despite certain mitigation on the APACHE II score and inflammatory response [ 15 ], it is mostly substituted by cephalosporins with higher potency due to its suboptimal efficacy, which increases the risk of adverse effects and the development of drug-resistant bacteria [ 16 ]. As a result, “step-down treatment” was recommended as a sensible medication approach for antimicrobial drug usage in ICU patients with severe bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…These adverse effects can compromise quality of life, increase financial costs, diminish adherence to treatment and cause medical complications [3,4]. In addition, the financial costs of managing side effects of chemotherapy and the demand for better health care are increasing, potentially compromising cancer treatment [5].…”
Section: Introductionmentioning
confidence: 99%
“…Within the health and illness sector, social constructionism has been used to examine meaning-making processes of the everyday subjective experiences of individuals with cancer through treatment and survivorship (Conrad & Barker, 2010). Within research with people with cancer specifically, past research has looked at how knowledge around cancer and chemotherapy are shaped by different cultural contexts and how these shape peoples' constructions of identity and access to healthcare (Chen et al, 2013;Gibson et al, 2022). For example, Chen et al (2013) and Gibson et al (2022) found that prevalent cultural norms and values played a significant role in shaping an individual's meaning making and experience regarding cancer and cancer treatment.…”
Section: Cancer Research Using Social Constructionismmentioning
confidence: 99%
“…Within research with people with cancer specifically, past research has looked at how knowledge around cancer and chemotherapy are shaped by different cultural contexts and how these shape peoples' constructions of identity and access to healthcare (Chen et al, 2013;Gibson et al, 2022). For example, Chen et al (2013) and Gibson et al (2022) found that prevalent cultural norms and values played a significant role in shaping an individual's meaning making and experience regarding cancer and cancer treatment. In cultures with a positive view on chemotherapy (such as western cultures), there was more acceptance towards undergoing treatment (Chen et al, 2013).…”
Section: Cancer Research Using Social Constructionismmentioning
confidence: 99%
See 1 more Smart Citation